Aqueous tape casting of micro and nano YSZ for SOFC electrolytes - Baquero, Tomas
Yttria-stabilized zirconia (YSZ) thick films with similar to 95% relative density were produced by aqueous tape casting to be used as electrolytes in solid oxide fuel cells (SOFC). Structural and morphologic properties of green and sintered bodies were analyzed starting from different particle size 8% yttria-stabilized zirconia powders. XRD showed the precursor powders to be single phase and nanocrystqlline with composition within the expected range for cubic YSZ. Grain size distribution and specific area measurements confirmed the micrometer and nanometer range of the particles. Before casting, slurries were formulated based on rheological characterization, zeta potential and pH measurements. A relationship between starting powders, ceramic suspensions and sintered bodies was established and adapted to the tape casting process. (C) 2013 Elsevier Ltd and Techna Group S.r.l. All rights reserved.